Exploring Capabilities for the Smart Service Transformation in Manufacturing: Insights from Theory and Practice - Koldewey, Christian; Fichtler, Timm; Scholtysik, Michel; Biehler, Jan; Schreiner, Nick; Sommer, Franziska; Schacht, Maximilian; Kaufmann, Jonas; Rabe, Martin; Sedlmeier, Joachim; Dumitrescu, Roman
Digital Servitization is one of the significant trends affecting the manufacturing industry. Companies try to tackle challenges regarding their differentiation and profitability using digital services. One specific type of digital services are smart services, which are digital services built on data from smart products. Introducing these kinds of offerings into the portfolio of manufacturing companies is not trivial. Moreover, they require conscious action to align all relevant capabilities to realize the respective business goals. However, what capabilities are generally relevant for smart services remains opaque. We conducted a systematic literature review to identify them and extended the results through an interview study. Our analysis results in 78 capabilities clustered among 12 principles and six dimensions. These results provide significant support for the smart service transformation of manufacturing companies and for structuring the research field of smart services.
Keywords: Digital Servitization; Transformation; Capabilities; Maturity; Smart Services

Business strategy taxonomy and solution patterns for the circular economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Data-Driven Product Management: A Practitioner-Driven Research Agenda - Grigoryan, Khoren; Fichtler, Timm; Schreiner, Nick; Rabe, Martin; Panzner, Melina; Kühn, Arno; Dumitrescu, Roman; Koldewey, Christian (Procedia CIRP 33)
The global megatrends of digitization and sustainability lead to new challenges for the design and management of technical products in industrial companies. Product management - as the bridge between market and company - has the task to absorb and combine the manifold requirements and make the right product-related decisions. In the process, product management is confronted with heterogeneous information, rapidly changing portfolio components, as well as increasing product, and organizational complexity. Combining and utilizing data from different sources, e.g., product usage data and social media data leads to promising potentials to improve the quality of product-related decisions. In this paper, we reinforce the need for data-driven product management as an interdisciplinary field of action. The state of data-driven product management in practice was analyzed by conducting workshops with six manufacturing companies and hosting a focus group meeting with experts from different industries. We investigate the expectations and derive requirements leading us to open research questions, a vision for data-driven product management, and a research agenda to shape future research efforts.
Keywords: Product Management; Data Analytics; Data-Driven Design; Product-related data; Lifecycle Data; Tool-support

Interview Study on Strategy Options for Platform Operation in B2B Markets - Özcan, Leon; Fichtler, Timm; Kasten, Benjamin; Koldewey, Christian; Dumitrescu, Roman
Keywords: Digital Platform; Platform Strategy; Strategic Management; Platform Life Cycle; Interview Study; Business Model; Business-to-Business; Two-sided Market; Multi-sided Market

An Integrative View of the Transformations towards Sustainability and Digitalization: The Case for a Dual Transformation - Kürpick, Christian; Rasor, Anja; Scholtysik, Michel; Kühn, Arno; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Soziotechnisches Risikomanagement als Erfolgsfaktor für die Digitale Transformation - Menzefricke, Jörn Steffen; Gabriel, Stefan; Gundlach, Thomas; Hobscheidt, Daniela; Kürpick, Christian; Schnasse, Felix; Scholtysik, Michel; Seif, Heiko; Koldewey, Christian; Dumitrescu, Roman (Schwerpunkt Business Model Innovation)

Introduction to the Minitrack on Data-driven Services in Manufacturing: Innovation, Engineering, Transformation, and Management - Koldewey, Christian; Martin, Rabe; Dumitrescu, Roman; Winter, Johannes (Proceedings of the 56th Hawaii International Conference on System Sciences)

Datengestützte Produktplanung
Unter dem Einfluss der Digitalisierung wandeln sich mechatronische Produkte zunehmend in cyber-physische Systeme (CPS). Diese sind in der Lage, umfangreiche Daten während ihres Betriebs zu sammeln und über digitale Netzinfrastrukturen zur Verfügung zu stellen. Gemeinsam mit weiteren Daten aus der Betriebsphase versprechen sie wertvolle Erkenntnisse über das Produkt und dessen Nutzer, welche für die Hersteller der CPS insbesondere für die Planung zukünftiger Produktgenerationenrelevant sind. Die zielgerichtete Nutzung von Betriebsdaten in der strategischen Produktplanung stellt produzierende Unternehmen jedoch noch vor zahlreiche Herausforderungen, z. B. hinsichtlich der Identifizierung Erfolg versprechender Use Cases. Das vorliegende Buch greift diese Herausforderungen auf und stellt ein Instrumentarium vor, das produzierende Unternehmen zur datengestützten Produktplanung befähigt. Neben der Vorstellung praxiserprobter Methoden und Werkzeuge werden Einblicke in vier Pilotprojekte gegeben. Das Instrumentarium entstand im Forschungsprojekt „DizRuPt“, das vom Bundesministerium für Bildung und Forschung (BMBF) gefördert wurde.

Nachhaltigkeit durch Daten im MBSE: Einblick in die Entwicklung eines Modell-Empfehlungssystems - Tissen, Denis; Tschirner, Christian; Koldewey, Christian; Dumitrescu, Roman (Tag des Systems Engineering)

A process-model for tailoring prototyping of cyber-physical systems - Tissen, Denis; Koldewey, Christian; Dumitrescu, Roman

Integrative conceptualization of products and business models for the circular economy: A systematic literature review - Scholtysik, Michel; Koldewey, Christian; Rohde, Malte; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Einstieg in die Kreislaufwirtschaft: Integrative Planung von Produkten und Geschäftsmodellen - Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman; Pierenkemper, Christoph; Hensen, Christian

A Data Map for Product Creation: Tasks, Data Flows, and IT-Systems from the Initial Idea to the Start of Production - Ködding, Patrick; Tissen, Denis; Koldewey, Christian (Proceedings of the 56th CIRP Conference on Manufacturing Systems, CIRP CMS ‘23)

A Reference Process Model for Scenario-based Foresight - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the XXXII ISPIM Innovation Conference)

Enhancing Risk Management for Digitalisation Projects in the Context of Socio-Technical Systems - Menzefricke, Jörn Steffen; Koldewey, Christian; Dumitrescu, Roman (The Digital Twin of Humans)

The Role of Design in interdisciplinary Product Development – Challenges, Research Approaches and Further Research needs - Stöhr, Bernd; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract In global competition, companies are continuously searching for a competitive advantage. A growing number of companies have identified the design of their products as a major success factor. The promises for companies associated with outstanding design are extremely attractive, ranging from better customer experience to higher sales growth. But even though the advantages of design seem to be compelling, companies are still having difficulties in leveraging the benefits of design. In this paper, we want to identify the underlying challenges that explain this gap. We are especially interested in the role and challenges of design in interdisciplinary product development. Therefore, we perform a literature review that clarifies terminology, analyses research approaches and identifies challenges. We determine seven key challenges for design in interdisciplinary product development. Furthermore, we observe a limited scope of research approaches in the reviewed literature. Based on these findings, we propose three further research directions to strengthen the role of design in interdisciplinary product development in the future.

Designing Business Models for a Circular Economy - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The megatrend sustainability will significantly change the future value creation of manufacturing companies. Their current linear value creation models need to change to conform to the requirements of sustainability. To face the challenges the circular economy has emerged as a promising economic model. With the shift from a linear to a circular economy, companies have to adjust their current business models. However, they still lack knowledge and adequate methods to develop circular business models. Hence, the aim of the paper is a circular business model canvas (CBMC) for designing circular businesses. A systematic literature review was conducted to identify significant criteria for circular business models. The criteria were analyzed utilizing a qualitative content analysis to derive the business model elements required for the circular economy. Existing elements from the Business Model Canvas were enriched and five new elements, e.g., reverse logistics, were found. Then, the business model elements were logically arranged resulting in the CBMC. It guides companies to systematically develop business models for the circular economy. The CBMC was evaluated by applying it within a mediumsized company in the electronics sector.

Towards a Data-Driven Product Management – Concepts, Advantages, and Future Research - Fichtler, Timm; Grigoryan, Khoren; Koldewey, Christian; Dumitrescu, Roman (2023 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))
Megatrends, such as digitization or sustainability, are confronting the product management of manufacturing companies with a variety of challenges regarding the design of future products, but also the management of the actual products. To successfully position their products in the market, product managers need to gather and analyze comprehensive information about customers, developments in the products’ environment, product usage, and more. The digitization of all aspects of life is making data on these topics increasingly available – via social media, documents, or the internet of things from the products themselves. The systematic collection and analysis of these data enable the exploitation of new potentials for the adaption of existing products and the creation of the products of tomorrow. However, there are still no insights into the main concepts and cause-effect relationships in exploiting data-driven approaches for product management. Therefore, this paper aims to identify the main concepts and advantages of data-driven product management. To answer the corresponding research questions a comprehensive systematic literature review is conducted. From its results, a detailed description of the main concepts of data-driven product management is derived. Furthermore, a taxonomy for the advantages of data-driven product management is presented. The main concepts and the taxonomy allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.
Keywords: Product Lifecyle Management (PLM); Data Analytics; Data-driven Design; Engineering Management; Lifecycle Data

Strategische Planung des Einstiegs in die Plattformökonomie - Özcan, Leon; Drewel, Marvin; Koldewey, Christian; Dumitrescu, Roman (Digitalisierung: Fallstudien, Tools und Erkenntnisse für das digitale Zeitalter)

acatech Maturity Index Smart Services - Dumitrescu, Roman; Riemensperger, Frank; Schuh, Günther; Biehler, Jan; Frey, Anna; Hocken, Christian; Koldewey, Christian; Kühn, Arno; Rabe, Martin; Schacht, Maximilian; Comans, Sebastian; Fichtler, Timm; et al.

Circular Product-Service-System Ideation Canvas – A Framework for the Design of circular Product-Service-System Ideas - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Scenario-Based Foresight in the Age of Digital Technologies and AI - Ködding, Patrick; Koldewey, Christian; Dumitrescu, Roman (New Digital Work)

Scenario-based Foresight in the Age of Digitalization and Artificial Intelligence – Identification and Analysis of Existing Use Cases - Ködding, Patrick; Ellermann, Kai; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Introduction to the Data-driven Services in Manufacturing Minitrack - Exploring Management, Engineering, and Organizational Transformation - Koldewey, Christian; Dumitrescu, Roman; Rabe, Martin (Proceedings of the 55th Hawaii International Conference on System Sciences)

A Reference Process Model for Usage Data-Driven Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 55th Hawaii International Conference on System Sciences)
Cyber-physical systems generate and collect huge amounts of usage data during operation. Analyzing these data may enable manufacturing companies to identify weaknesses and learn about the users of their products. Such insights are valuable in the early phases of product development like product planning, as they facilitate decision-making for product improvement. The analysis and exploitation of usage data in product planning, however, is a new task for manufacturing companies. To reduce mistakes and improve the results, companies should build upon a suitable reference process model. Unfortunately, established models for analyzing data cannot be easily applied for product planning. In this paper, we propose a reference process model for usage data-driven product planning. It builds on three well-established models for analyzing data and addresses the unique characteristics of usage data-driven product planning. Finally, we customize the model for a manufacturing company and demonstrate how it could be implemented in practice.

Aligning strategic position, behavior, and structure for smart service businesses in manufacturing - Koldewey, Christian; Rasor, Anja; Reinhold, Jannik; Gausemeier, Jürgen; Dumitrescu, Roman; Chohan, Nadia; Frank, Maximilian (Technological Forecasting and Social Change)

Planning the Analysis of Use Phase Data in Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract The ongoing digitalization of products offers product managers new potentials to plan future product generations based on data from the use phase instead of assumptions. However, product managers often face difficulties in identifying promising opportunities for analyzing use phase data. In this paper, we propose a method for planning the analysis of use phase data in product planning. It leads product managers from the identification of promising investigation needs to the derivation of specific use cases. The application of the method is shown using the example of a manufacturing company.

How can Data Analytics Results be Exploited in the Early Phase of Product Development? 13 Design Principles for Data-Driven Product Planning - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (AMCIS 2022 Proceedings)
The megatrend digitalization turns mechatronic products into continuous collectors and generators of use phase data. By analyzing this data, manufacturers can uncover valuable insights about the products and the users. Especially in product planning, these insights could be used to plan promising future product generations. The systematic exploitation of data analytics results, however, represents a serious challenge, as research on the topic is still scarce. In this paper, we present 13 design principles for exploiting data analytics results in product planning. The results are based on a systematic literature review and a workshop with a research consortium. The evaluation of the design principles is demonstrated with a real case of a manufacturing company. The identified design principles represent a first contribution to a still scarcely explored research field.

17 Use Cases for Analyzing Use Phase Data in Product Planning of Manufacturing Companies - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Increasing Firm Performance through Industry 4.0—A Method to Define and Reach Meaningful Goals - Koldewey, Christian; Hobscheidt, Daniela; Pierenkemper, Christoph; Kühn, Arno; Dumitrescu, Roman (Sci)

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies - Meyer, Maurice; Fichtler, Timm; Koldewey, Christian; Dumitrescu, Roman (Artificial Intelligence for Engineering Design, Analysis and Manufacturing)
The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during their utilization. Analyzing these data could enable their manufacturers to generate and exploit insights concerning product performance and user behavior, revealing problems and potentials for improvement. However, research on analyzing use phase data in product planning of manufacturing companies is scarce. Therefore, we conducted an exploratory interview study with decision-makers of eight manufacturing companies. The result of this paper is a detailed description of the potentials and challenges that the interviewees associated with analyzing use phase data in product planning. The potentials explain the intended purpose and generic application examples. The challenges concern the products, the data, the customers, the implementation, and the employees. By gathering the potentials and challenges through expert interviews, our study structures the topic from the perspective of the potential users and shows the needs for future research.
Keywords: Artificial Intelligence; Industrial and Manufacturing Engineering

Software-gestützte Planung der Smart-Service-Transformation - Reinhold, Jannik; Siewert, Michael; Scholtysik, Michel; Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Smart Services eröffnen vielfältige Geschäftsmöglichkeiten für produzierende Unternehmen und erfordern zugleich einschneidende Anpassungen ihrer häufig historisch gewachsenen Wertschöpfung. Dieser Beitrag zeigt eine Web-Applikation, die es produzierenden Unternehmen erlaubt, die erforderliche Smart-Service-Transformation zu planen. Dafür werden umfassendes Lösungswissen bereitgestellt und eine individuelle Gestaltungsempfehlungen für die zukünftige Wertschöpfung als Smart-Service-Anbieter gegeben.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Value Creation Framework and Roles for Smart Services - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Adapting the product design to the circular economy using R-principles - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Datengestützte Projektplanung - Dumitrescu, Roman; Koldewey, Christian

Socio-technical risk management in the age of digital transformation – identification and analysis of existing approaches - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

UNDERSTANDING USAGE DATA-DRIVEN PRODUCT PLANNING: A SYSTEMATIC LITERATURE REVIEW - Meyer, Maurice; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Abstract Cyber-physical systems (CPS) are able the collect huge amounts of data about themselves, their users, and their environment during their usage phase. By feeding these usage data back into product planning, manufacturers can optimize their engineering and decision-making processes. Despite promising potentials, most manufacturers still do not analyze usage data within product planning. Also, research on usage data-driven product planning is scarce. Therefore, this paper aims to identify the main concepts, advantages, success factors and challenges of usage data-driven product planning. To answer the corresponding research questions, a comprehensive systematic literature review is conducted. From its results, a detailed description of usage data-driven product planning consisting of six main concepts is derived. Furthermore, taxonomies for the advantages, success factors and challenges of usage data-driven product planning are presented. The six main concepts and the three taxonomies allow for a deeper understanding of the topic while highlighting necessary future actions and research needs.

Zukunftsrobuste Weiterentwicklung von Produktportfolios: Erkenntnisse und Handlungsbedarfe aus der Praxis - Meyer, Maurice; Hemkentokrax, Jan-Philipp; Koldewey, Christian; Dumitrescu, Roman; Tröster, Peter M.; Schlegel, Michael; Kling, Christopher L.; Rapp, Simon; Albers, Albert (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)

Towards Identifying Data Analytics Use Cases in Product Planning - Meyer, Maurice; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

Die Kraft von Startup-Partnerschaften für das Innovationssystem eines Automobilzulieferers - Hemkentokrax, Jan-Philipp; Eckelt, Daniel; Haarmann, Lennard; Koldewey, Christian; Dumitrescu, Roman (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)

Smart Service-Transformation - Den Wandel der Wertschöpfung erfolgreich gestalten - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman; Rausch, Gerhard (Vorausschau und Technologieplanung - 16. Symposium Vorausschau und Technologieplanung)

Identifying Value Creation Patterns for Smart Services - Reinhold, Jannik; Ködding, Patrick; Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)

SUSTAINABILITY THROUGH THE DIGITALIZATION: EXPLORING POTENTIALS AND DESIGNING VALUE CO-CREATION ARCHITECTURES FOR PRODUCT-SERVICE-SYSTEMS - Scholtysik, Michel; Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Digitalization and sustainability are major challenges for today's manufacturing industry. While digitalization is characterized by the incorporation of digital technologies in the products and services as well as the value creation architectures, sustainability requires them to balance economic, environmental and social issues. In both areas, especially Product Service Systems (PSS) are constantly gaining importance. This results in so called smart PSS that integrate digital technologies as well as sustainable PSS which aim at a positive impact on sustainability. Both two concepts cannot be clearly delimited since smart PSS might be designed for sustainability as well and sustainable PSS might be used with digital technologies. This paper aims to investigate the interrelations. To that, digitalization patterns of products and services are evaluated regarding their sustainable impact. The evaluation is conducted by a survey in research and industry. Furthermore, the design of the underlying value creation architecture is investigated. Here, a methodology is proposed enabling companies to optimize their value creation architecture.
Keywords: sustainability

Smart Service-Transformation mit Geschäftsmodellmustern - Reinhold, Jannik; Ködding, Patrick; Scholtysik, Michel; Koldewey, Christian; Dumitrescu, Roman (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
Abstract Smart Services sind das Resultat zweier Megatrends: Digitalisierung und Servitisierung. Diese digitalen Dienstleistungen erfordern innovative Geschäftsmodelle, deren Umsetzung jedoch häufig eine Anpassung historisch gewachsener Wertschöpfung produzierender Unternehmen voraussetzt. Wir liefern geeignete Geschäftsmodellmuster zur Entwicklung von Geschäftsmodellen für Smart Services und zeigen, wie produzierende Unternehmen darauf aufbauend die Transformation ihrer Wertschöpfung planen können.

Development Process for Smart Service Strategies: Grasping the Potentials of Digitalization for Servitization - Koldewey, Christian; Gausemeier, Jürgen; Dumitrescu, Roman; Evers, Hans Heinrich; Frank, Maximilian; Reinhold, Jannik (Digitalization)

Development Process for Smart Service Strategies: Grasping the Potentials of Digitalization for Servitization - Koldewey, Christian; Gausemeier, Jürgen; Dumitrescu, Roman; Evers, Hans-Heinrich; Frank, Maximilian; Reinhold, Jannik (Digitalization)

Systematik zur Entwicklung von Smart Service-Strategien im produzierenden Gewerbe - Koldewey, Christian
Mit der zunehmenden Bedeutung von digitalen Lösungen und innovativen Dienstleistungen geht eine signifikante Transformation des produzierenden Gewerbes einher. Die Digitalisierung führt zu intelligenten Produkten, die Daten generieren und über das Internet austauschen. Auf Basis dieser Daten können Produkthersteller gänzlich neue digitale Dienstleistungen anbieten, sogenannte Smart Services. Ihre erfolgreiche Umsetzung ist essentiell, um in der Wettbewerbsarena der Zukunft bestehen zu können. Die Gestaltung eines Smart Service-Geschäfts ist jedoch nicht trivial. Ziel der vorliegenden Arbeit ist eine Systematik zur Entwicklung von Smart Service-Strategien im produzierenden Gewerbe. Die Systematik besteht aus drei Bestandteilen: der Erste ist die Konzeption von Smart Service-Strategien im Sinne eines Referenzmodells. Sie definiert die auszugestaltenden Aspekte. Der Zweite ist das Gestaltungswissen. Es werden Normstrategien und Funktionalitäten im Kontext von Smart Services für die Strategieentwicklung bereitgestellt. Die Strategieentwicklung wird im dritten Bestandteil adressiert, einer Methode bestehend aus einem Vorgehensmodell und unterstützenden Hilfsmitteln. Das Vorgehensmodell orchestriert den Einsatz der Hilfsmittel und des Gestaltungswissens. Resultat ist eine Smart Service-Strategie, die die Vision für das Smart Service-Geschäft sowie den Weg zu deren Realisierung darstellt. Die Systematik wurde anhand eines Unternehmens des Sondermaschinenbaus erfolgreich validiert.
Keywords: Smart Service; Strategie

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Jörn Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Chohan, Nadia; Reinhold, Jannik (ZWF, Zeitschrift für wirtschaftliche Fabrikplanung 115(7-8))
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbruegger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP (91))

Pattern‐based development of digital platforms - Drewel, Marvin; Özcan, Leon; Koldewey, Christian; Gausemeier, Jürgen (Creativity and Innovation Management)

Pattern‐based development of digital platforms - Drewel, Marvin; Özcan, Leon; Koldewey, Christian; Gausemeier, Jürgen (Creativity and Innovation Management)

A reference process for the Smart Service business: development and practical implications - Frank, Maximilian; Gausemeier, Juergen; Hennig-Cardinal von Widdern, Nils; Koldewey, Christian; Menzefricke, Joern Steffen; Reinhold, Jannik (Proceedings of the ISPIM connects)

Scaling Digital Business Models: A Case from the Automotive Industry - Becker, Julia-Kristin; Joachim, Klemens; Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the 2020 ISPIM Innovation Conference (Virtual) Event "Innovating in Times of Crisis")

In-depth Analysis of the Effects of Smart Services on Value Creation - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Buss, Eugen (Proceedings of the ISPIM Connects Bangkok – Partnering for an Innovative Community)

Aligning Strategy and Structure for Smart Service Businesses in Manufacturing - Koldewey, Christian; Gausemeier, Jürgen; Chohan, Nadia; Frank, Maximilian; Reinhold, Jannik; Dumitrescu, Roman (Proceedings of the IEEE International Conference on Technology Management, Operations and Decisions ”Disruptive Technologies and Social Impacts”)

Systematische Entwicklung von Normstrategien für Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen; Bäsecke, Alexander; Reinhold, Jannik; Dumitrescu, Roman (ZWF Zeitschrift für wirtschaftliche Fabrikplanung)
Die Verfügbarkeit von Daten aus dem Betrieb hat durch die Einführung von vernetzten intelligenten Fertigungssystemen (cyber-physische Systeme) stark zugenommen. Hieraus eröffnen sich Erfolg versprechende Möglichkeiten für Smart Services und damit verbundene neue Geschäftsfelder. Voraussetzung für den Eintritt in ein neues Geschäft mit Smart Services ist eine fundierte Geschäftsstrategie. Wir zeigen die zentralen Gestaltungsfelder von Smart Service-Strategien auf und erläutern, wie sechs von uns ermittelte Normstrategien bei der Formulierung einer attraktiven Strategie helfen können.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

Planning a Smart Service Business Integrating External Partners - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Managing Digital Open Innovation)
Today’s manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding business models and value networks fundamentally differ from traditional ones. Developing smart services requires an advanced management of business models and new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to extend their business model portfolios and adapt their value networks. However, the highly complex transformation of value creation especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this chapter, we introduce a basic framework for designing smart services and present a methodology for the planning of a smart service business integrating external partners. The methodology is structured into five phases: Examination of smart service portfolio, analysis of business models and environment, business model portfolio planning, competence identification and analysis, and value creation planning. The methodology is explained by an example on cable marker printers.
Keywords: Smart Service; Digitalisierung; Industrie 4.0

GEMINI-Modellierungssprache für Wertschöpfungssysteme - Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

GEMINI-Geschäftsmodellmuster-Kartenset - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodellvalidierung - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Geschäftsmodell-Roadmapping - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman (Der Geschäftsmodell-Toolguide)

Framework and Functionality Patterns for Smart Service Innovation - Koldewey, Christian; Meyer, Maurice; Stockbrügger, Patrick; Dumitrescu, Roman; Gausemeier, Jürgen (Procedia CIRP)

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; von Enzberg, Sebastian; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Proceedings of the CIRP DESIGN)
One of the notable drivers of the fourth industrial revolution is the collection of vast amounts of data along the entire lifecycle of a product. The analysis of product lifecycle data in conjunction with product hypotheses leads to promising potentials in strategic product planning. In this thesis paper, we postulate the need for data-driven product generation and retrofit planning as an interdisciplinary field of research. We define and analyze the key concepts and derive requirements in a structured way. Based on an exhaustive research of existing approaches, we structure open research questions and propose a roadmap in order to shape future research efforts.

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects)
Today's manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding value networks fundamentally differ from traditional ones. Developing smart services requires new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to adapt their value networks. However, the highly complex transformation of value crea-tion especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this paper, we introduce a basic framework for planning smart services and present a methodology for competence-based plan-ning of value networks for smart services in three phases: Smart service analysis, competence analysis and value creation planning. The methodology is explained by an example from tooling machine industry.

Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)
Smart Services are digital, IT-based services that are using data of a corresponding physical product, e.g. predictive maintenance or automated reordering of consumables for a production machine. This contribution shows a study about 265 services from the German manufacturing industry. We derive hypothesis for identifying Smart Services as well as eleven variables and their 47 characteristics to systematically describe them. A clustering of the found Smart Services resulted in four distinguishable groups. Furthermore, we show statistics of how companies combine the characteristics of their market offerings. Our findings reflect where the theoretical possibilities were fully met by the implementations of the German manufacturing companies and where the industry is still lagging behind. Finally, we derived six bundles of highly consistent combinations of the characteristics. These bundles can be starting points for developing Smart Services for one’s specific use case.

Significance and Challenges of Data-driven Product Generation and Retrofit Planning - Massmann, Melina; Meyer, Maurice; Dumitrescu, Roman; Enzberg, Sebastian von; Frank, Maximilian; Koldewey, Christian; Kühn, Arno; Reinhold, Jannik (Procedia CIRP)

Gestaltung hybrider Wertschöpfung und Arbeit im Kontext von Smart Services - Koldewey, Christian; Reinhold, Jannik; Dumitrescu, Roman; Frank, Maximilian; Schweppe, Thomans; Melzer, Annegret (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Strategie als Erfolgsfaktor - Koldewey, Christian; Dumitrescu, Roman (ServiceToday)

Development Process for Smart Service Strategies - Koldewey, Christian; Evers, Hans Heinrich; Dumitrescu, Roman; Frank, Maximilian; Gausemeier, Jürgen; Reinhold, Jannik (Proceedings of The XXX ISPIM INNOVATION CONFERENCE)

Classification-based Planning of Smart Service Portfolios - Frank, Maximilian; Rabe, Martin; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen; Hennig-Cardinal von Widdern, Nils; Reinhold, Jannik (Proceedings of the ISPIM connects)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects Ottawa – Innovation for Local and Global Impact)

Smart Service-Innovationen - Gewusst wie - Koldewey, Christian; Reinhold, Jannik; Willmes, Georg; Michels, Jan Stefan (markt & wirtschaft westfalen - Das Wirtschaftsmagazin für zukunftsorientierte Unternehmer)

Entwicklung von Smart Service Strategien - Koldewey, Christian; Gausemeier, Jürgen; Fischer, Stefan; Kage, Martin (Symposium für Vorausschau und Technologieplanung)

Competence-based Planning of Value Networks for Smart Services - Reinhold, Jannik; Frank, Maximilian; Koldewey, Christian; Dumitrescu, Roman; Gausemeier, Jürgen (Proceedings of the ISPIM Connects)
Today's manufacturing industry is confronted with fundamental changes in value creation. The tension between the two megatrends of digitization and servitization leads to new hybrid market offerings, so-called smart services. Corresponding value networks fundamentally differ from traditional ones. Developing smart services requires new competences in young disciplines, while their provision requires new internal and external organizational structures or processes. To strengthen their competitive position, manufacturing companies need to adapt their value networks. However, the highly complex transformation of value crea-tion especially challenges small and medium-sized companies due to limited competences and resources. They must consider opening their boundaries and collaborating with partners. In this paper, we introduce a basic framework for planning smart services and present a methodology for competence-based plan-ning of value networks for smart services in three phases: Smart service analysis, competence analysis and value creation planning. The methodology is explained by an example from tooling machine industry.

Pattern based development of digital platforms - Drewel, Marvin; Gausemeier, Jürgen; Koldewey, Christian; Özcan, Leon (Proceedings of the 2018 ISPIM Connects)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)

Applying Open Innovation in the Field of Aircraft MRO - Insights from the LOMIS Project - Pieper, Thorsten; Echterfeld, Julian; Koldewey, Christian (Book of Abstracts of the 16th International Open and User Innovation Conference, 6. - 8. Aug. 2018)

Planning of scalable Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen (Proceedings of the 2018 ISPIM Innovation Conference)

Smart Services - Konzept einer neuen Marktleistung - Frank, Maximilian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb 113(5))
Smart Services sind digitale Dienstleistungen, die aus den Daten einer Sachleistung Mehrwert generieren. Durch eine übersichtliche Abgrenzung der kursierenden Begrifflichkeiten tragen wir zum Verständnis dieser neuartigen Marktleistung bei. Wir zeigen eine Referenzarchitektur und postulieren vier Hauptherausforderungen: Konzipierung, Kompetenzen, Skalierung, strategische Planung.

Approach for a Pattern-Based Development of Frugal Innovations - Lehner, Anne-Christin; Koldewey, Christian; Gausemeier, Jürgen (Technology Innovation Management Review 8(4))

Approach for a Pattern-Based Development of Frugal Innovations - Lehner, Anne-Christin; Koldewey, Christian; Gausemeier, Jürgen (Technology Innovation Management Review)

Smart Services – Konzept einer neuen Marktleistung - Frank, Maximillian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Business Model Portfolio Planning for Smart Services - Koldewey, Christian; Echterfeld, Julian; Reilender, Meikel; Gausemeier, Jürgen (Proceedings of the ISPIM connects)

Pattern based development of digital platforms - Drewel, Marvin; Gausemeier, Jürgen; Koldewey, Christian; Özcan, Leon (Proceedings of the 2018 ISPIM Connects)

Applying Open Innovation in the Field of Aircraft MRO - Insights from the LOMIS Project - Pieper, Thorsten; Echterfeld, Julian; Koldewey, Christian (Book of Abstracts of the 16th International Open and User Innovation Conference, 6. - 8. Aug. 2018)

Planning of scalable Smart Services - Koldewey, Christian; Frank, Maximilian; Gausemeier, Jürgen (Proceedings of the 2018 ISPIM Innovation Conference , Jun. 2018 International Society for Professional Innovation Management (ISPIM))

Smart Services - Konzept einer neuen Marktleistung - Frank, Maximilian; Koldewey, Christian; Rabe, Martin; Dumitrescu, Roman; Gausemeier, Jürgen; Kühn, Arno (ZWF Zeitschrift für wirtschaftlichen Fabrikbetrieb)

Geschäftsideen finden für Industrie 4.0 - Integrative Entwicklung von Geschäftsmodellen und Wertschöpfungssystemen - Gausemeier, Jürgen; Koldewey, Christian; Echterhoff, Benedikt (mav - Innovation in der spanenden Fertigung)

Einführung von Industrie 4.0 in die Miele Produktion – Ein Erfahrungsbericht - Gausemeier, Pia; Frank, Maximilian; Koldewey, Christian (Wissenschaftsforum Intelligente Technische Systeme (WInTeSys) 2017, Band 369)

Mit Industrie 4.0 zum Unternehmenserfolg - Integrative Planung von Geschäftsmodellen und Wertschöpfungssystemen

Pattern based business model development – identification, structuring and application of business model patterns - Echterhoff, Benedikt; Koldewey, Christian; Gausemeier, Jürgen (Proceedings of the ISPIM Innovation Forum, Mrz. 2017 International Society for Professional Innovation Management (ISPIM))

Integrative Entwicklung von Smart Services und Geschäftsmodellen am Beispiel von Werkzeugmaschinen - Haggenmüller, Wolfgang A.; Martin, Stefan; Preisinger, Markus; Echterhoff, Benedikt; Koldewey, Christian (Vorausschau und Technologieplanung, Band 360)

Geschäftsmodelle für Industrie 4.0 - Digitalisierung als große Chance für zukünftigen Unternehmenserfolg - Echterhoff, Benedikt; Gausemeier, Jürgen; Koldewey, Christian; Mittag, Tobias; Schneider, Marcel; Seif, Heiko (Digital vernetzt. Transformation der Wertschöpfung.: Szenarien, Optionen und Erfolgsmodelle für smarte Geschäftsmodelle, Produkte und Services)

Vorausschau von Stakeholder-Verhalten mit der Szenario-Technik - Peter, Stefan; Gausemeier, Jürgen; Amshoff, Benjamin; Koldewey, Christian (Symposium für Vorausschau und Technologieplanung, Band 347 , Kapitel: 1)
Strategische Planung ermöglicht es, frühzeitig auf sich ändernde Markt- und Wettbe-werbsbedingungen zu reagieren. Für strategische Entscheidungen wird eine Vorstellung von der Zukunft benötigt. Das zukünftige Verhalten von Wettbewerbern, Lieferanten, Kunden, Verbänden etc. (Stakeholder) ist dabei eine wesentliche Einflussgröße. Dies birgt große Unsicherheit bzgl. konkreter Entscheidungsprobleme (z.B. Produktstrategie: Wie soll der Wettbewerbsvorsprung über die Produktlebensdauer erhalten bleiben?). Wie diese Stakeholder auf strategische Entscheidungen reagieren, lässt sich allerdings nicht ohne weiteres vorhersagen (z.B. Preiskampf, Innovations-Offensive). Das Fortschreiben bisherigen Verhaltens kann zu Fehleinschätzungen führen. Somit ist es notwendig das Verhalten der relevanten Stakeholder systematisch vorauszudenken. Dabei hilft die Szenario-Technik mögliche Reaktionen zu antizipieren. Wir schlagen ein Vorgehen vor, das sich aus Stakeholder-Analyse und Szenario-Technik zusammensetzt. Dabei zeigen wir, wie Stakeholder identifiziert werden, die den größten Einfluss auf den Erfolg der gewählten Entscheidung haben. Dabei spielen Reaktions-neigung und Betroffenheit eine wesentliche Rolle. Für die relevanten Stakeholder wer-den Verhaltens-Szenarien erstellt. Dazu können ausgehend von einem Katalog Positio-nierungsvariablen mit unterschiedlichen Handlungsoptionen ausgewählt und um situati-onsbedingte Variablen angereichert werden. Die Verhaltens-Szenarien geben Aufschluss über mögliche, konsistente Verhaltensweisen der Stakeholder. Abschließend erläutern wir, wie Referenz-Szenarien auf Basis des Stakeholder-Charakters ausgewählt werden und wie daraus Rückschlüsse für die eigene Entscheidung getroffen werden können.